Comparative effect of tumour necrosis factor inhibitors versus other biological agents on cardiovascular risk-associated biomarkers in patients with rheumatoid arthritis. Issue 2 (21st July 2019) - Virone, Alexandre; Bastard, Jean-Philippe; Fellahi, Soraya; Capeau, Jacqueline; Rouanet, Stéphanie; Sibilia, Jean; Ravaud, Philippe; Berenbaum, Francis; Gottenberg, Jacques-Eric; Sellam, Jérémie
Abstract : Background: To comparatively investigate the differential effect of second-line tumour necrosis factor inhibitors (TNFis) versus other biological agents on cardiovascular disease (CVD) risk-associated biomarkers in patients with rheumatoid arthritis (RA). Methods: We evaluated the serum levels of lipoprotein-associated apoproteins ApoA1 and ApoB100 and lipoprotein(a) (Lp(a)) and the leptin/adiponectin ratio (LAR) as an insulin resistance proxy in patients with RA from the Rotation Or Change (ROC) trial treated with either a second-line TNFi or another biologic (tocilizumab (TCZ), rituximab or abatacept) at baseline and week 24. We compared the changes in biomarker levels in each group and according to the EULAR response. Results: Of the 300 patients enrolled in the ROC trial, 203 were included in the study, including 96 in the second-line TNFi group and 107 in the other biological group. The measured biomarkers did not deteriorate between baseline and week 24 regardless of the group. A greater improvement in the LAR was noted in the other biological group (median (IQR) −0.12 ng/µg (−0.58 to 0.31) vs 0.04 (−0.19 to 0.43), p=0.033), and a greater improvement in the Lp(a) level was observed following treatment with TCZ than with a TNFi (−0.05 g/L (−0.11 to −0.01) vs −0.01 g/L (−0.02 to 0.01), p<0.001). When considering the patients' responses to treatment, improved biomarkers were mainly observed in the EULAR responders in each treatment group. Conclusions: TNFis and non-TNFis were neutral on improved CVD risk-associated biomarkers in patients with RA insufficiently controlled by TNFis. TCZ could be associated with a better improvement concerning Lp(a) and LAR than TNFis. This improvement could be related to a good therapeutic response, thereby supporting the need of good control of RA. Trial registration number: ClinicalTrials.gov Identifier NCT01000441, registered on 22 October 2009.